Israel's anti-liberal coalition: The new government is seeking fundamental changes in the political system and in the Israeli-Palestinian conflict - Peter Lintl (Stiftung Wissenschaft und Politik (SWP), 2023)
The new government in Israel is politically further to the right than any other before it. The success of the radical right parties and their inclusion in the government are the results of a long-term transformation of Israel's political landscape. One characteristic of this development is the genesis of a right-wing majority, accompanied by a shift to the right of the mainstream, and the political legitimisation of the most radical segment of Israeli society. The common denominator of this government is its anti-liberal impetus, which amounts to a reorganisation of the state. The government intends to weaken democratic mechanisms, especially the system of checks and balances, the status of the Supreme Court, and that of fundamental rights. Instead, majoritarian principles are to be strengthened, placing few limits on government majorities. This disruptive approach also applies to the conflict with the Palestinians. Here, victory is sought: The integration of the West Bank into the legal territory of the state of Israel is to be made irreversible.
Keywords: 320; Israel; Benjamin Netanyahu; Betzalel Smotrich; Itamar Ben-Gvir; Michael Ben-Ari; Likud; Israel Beitenu; Religios Zionism; Otzma Yehudit; Noam; ultra-Orthodox parties; Shas; Haredim; United Tora Judaism; majoritarian democracy; West Bank; annexation; halacha